Sporadic Gene Loss After Duplication Is Associated with Functional Divergence of Sirtuin Deacetylases Among Candida Yeast Species. Issue 10 (1st October 2016) - Rupert, Christopher B; Heltzel, Justin M H; Taylor, Derek J; Rusche, Laura N
Abstract: Gene duplication promotes the diversification of protein functions in several ways. Ancestral functions can be partitioned between the paralogs, or a new function can arise in one paralog. These processes are generally viewed as unidirectional. However, paralogous proteins often retain related functions and can substitute for one another. Moreover, in the event of gene loss, the remaining paralog might regain ancestral functions that had been shed. To explore this possibility, we focused on the sirtuin deacetylase SIR2 and its homolog HST1 in the CTG clade of yeasts. HST1 has been consistently retained throughout the clade, whereas SIR2 is only present in a subset of species. These NAD + -dependent deacetylases generate condensed chromatin that represses transcription and stabilizes tandemly repeated sequences. By analyzing phylogenetic trees and gene order, we found that a single duplication of the SIR2/HST1 gene occurred, likely prior to the emergence of the CTG clade. This ancient duplication was followed by at least two independent losses of SIR2 . Functional characterization of Sir2 and Hst1 in three species revealed that these proteins have not maintained consistent functions since the duplication. In particular, the rDNA locus is deacetylated by Sir2 in Candida albicans, by Hst1 in C. lusitaniae, and by neither paralog in C. parapsilosis . In addition, the subtelomeres in C. albicans are deacetylated by Sir2 rather than by Hst1, which is orthologous to the sirtuin associated with Saccharomyces cerevisiae subtelomeres. These differences in function support the model that sirtuin deacetylases can regain ancestral functions to compensate for gene loss.